Effect of disturbance on plant species diversity in moist tropical forest of eastern Nepal (Our Nature, 2018)
Species diversity is a key factor for the stability of ecosystems but the increasing disturbances in tropical forests resulted in the shrinkage of biological diversity. This study was conducted in undisturbed and disturbed stands of Sal (Shorea robusta Gaertn.) dominated moist tropical forest of Sunsari district, eastern Nepal in order to understand the herb, shrub and tree diversity. Present study reported the 47, 16 and 60 species of herbs, shrubs and trees, respectively. The species richness and the Shannon–Wiener index for tree species were higher in undisturbed forest (9.11 and 3.08, respectively), while the Simpson’s index (index of dominance) was higher in disturbed forest (0.11).  On the other hand, reverse case was found for shrubs and herbs where species richness and Shannon–Wiener index were higher but index of dominance was lower in disturbed forest. Changes in species diversity pattern reflect the effect of disturbance.